2021
DOI: 10.2147/ijwh.s296310
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric Patients and Healthcare Providers Perspectives to Inform Mobile App Design for Physical Activity and Weight Control During Pregnancy and Postpartum in a Rural Setting

Abstract: Background Mobile health technology offers the opportunity for women to engage with physical activity promotion programs without many of the barriers commonly associated with exercise during and after pregnancy (eg, childcare concerns, rigid schedules, fear of doing harm to fetus or self, access to fitness facilities, uncomfortable with body in front of others) which may be particularly useful in under-resourced rural environments. We conducted the first known study on perspectives of pregnant wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 70 publications
(111 reference statements)
1
22
0
1
Order By: Relevance
“…This may be particularly useful in under‐resourced rural environments. 105 It is important that design and usability of these e‐health interventions is relevant to women from diverse cultural backgrounds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may be particularly useful in under‐resourced rural environments. 105 It is important that design and usability of these e‐health interventions is relevant to women from diverse cultural backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…This may be particularly useful in under-resourced rural environments. 105 It is important that design and usability of these e-health interventions is relevant to women cultural backgrounds. While this paper focuses on factors influencing individual-level behaviour change, several important systemic barriers were identified, including accessibility, flexibility and safety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apps for pregnancy and postpartum have an overall quality mean of 3.06 according to the same instrument, lower when compared to health apps in general (3.74). Among the items, functionality is the area with the best assessment in the applications and stands out with higher means, while engagement, information and aesthetics have lower means ( 24 , 25 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Several types of mobile applications designed and developed to help parents to engaged with pre and post-delivery problems’ and complications ( 19 22 ). The authors concluded there are no available applications that address a variety of infant feeding subjects ( 23 ).…”
Section: Introductionmentioning
confidence: 99%